The Ecology of Erotic Passion: The Case of Trachiniae - Perodaskalakis, Dimitris (Ariadne, 2026)
Undeniably, erotic passion in Trachiniae is symbolized in the context of not only ritual practices (transitional marriage ceremonies) but also natural places, and therefore natural forces, which seal the tragic discourse as fields of reference with a mythological background and an interpretatively open historical and political horizon. In this paper I focus on the way in which references to natural places and natural imagery in general acquire additional ecocritical, ecotheological and ultimately political connotations in the historical time of the work’s writing and performance, if this is connected to Pericles and his legendary love passion for Aspasia. We will therefore be concerned with the way in which the mythical ecology of the dramatic landscape is highlighted in its connections with tragic passion and in its echoes of the historical events of the era.